2012
DOI: 10.1177/1352458512443092
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilaments as biomarkers in multiple sclerosis

Abstract: Neurodegeneration is the correlate of disease progression in multiple sclerosis (MS) and thus biological biomarkers that sensitively reflect this process are much needed. Neurofilament protein subunits are potential cerebrospinal fluid (CSF) biomarkers for disease progression in MS. We argue that the neurofilament light subunit can reflect acute axonal damage mediated by inflammatory mechanisms and can imply prognostic value for conversion from clinically isolated syndrome (CIS) to definite MS. The neurofilame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
189
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(194 citation statements)
references
References 39 publications
(85 reference statements)
4
189
1
Order By: Relevance
“…NF-L levels have been found to reflect acute axonal damage and NF-H chronic irreversible damage, therefore implying prognostic value for disease progression or disability [23]. In addition, immunosuppression therapies using Natalizumab or Fingolimod have been evaluated using soluble NF-L and NF-H levels in CSF with interesting results [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…NF-L levels have been found to reflect acute axonal damage and NF-H chronic irreversible damage, therefore implying prognostic value for disease progression or disability [23]. In addition, immunosuppression therapies using Natalizumab or Fingolimod have been evaluated using soluble NF-L and NF-H levels in CSF with interesting results [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Neurofilament subunits and fragments that are released during neuronal damages may even be processed in disease specific ways. However, neurofilament detection assays still have to be refined to increase sensitivity and specificity [6,37,50].…”
Section: Biomarker Candidates In the Central Nervous Systemmentioning
confidence: 99%
“…[7][8][9] There is evidence showing that both CSF and serum Nfs levels are associated with disease activity, physical disability, and magnetic resonance imaging (MRI) changes in MS; however, clinical follow-up time was relatively short in most of these studies. 1,2,7 In a recent study in 51 MS patients, it has been shown that higher CSF NfH values could prognosticate an unfavourable disease evolution during a follow-up time of 15 years. 3 Another study in 95 MS cases with a median follow-up time of 14 years could demonstrate that elevated CSF NfL levels were predictive of future physical disability.…”
mentioning
confidence: 99%
“…3 Nf belong to intermediate filament proteins and consist of three isotypes, which are a neurofilament light (NfL) chain of 68 kDa, a neurofilament intermediate (NfM) chain of 150 kDa, and a neurofilament heavy (NfH) chain of 190-210 kDa. 1 Evidence for increased Nf levels in MS mainly exists for NfL and NfH, whereas NfM has not been extensively studied so far. 4 Analysis of Nf levels was so far limited to cerebrospinal fluid (CSF), because detection systems were not sensitive enough to measure the generally lower concentration of Nf in blood samples.…”
mentioning
confidence: 99%